National Education Based on the Concept of the Pancasila Legal State as a Form of Character Formation for a Dignified National Civilization - Casnika, Casnika (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
National Education is an education based on Pancasila and the 1945 Constitution of the Republic of Indonesia, which is rooted in religious values, Indonesian national culture and responsiveness to the demands of changing times. To realize this ideal, the struggle of the community, the government, and the implementation of Education is needed. National education functions to develop abilities and form the character and civilization of a dignified nation in order to educate the life of the nation. The application of education based on Pancasila values is very important to improve the quality of education in Indonesia and form a better student character. Therefore, the government, educators, and non-formal educational institutions need to continue to work together and be committed to developing and implementing Pancasila values in the Indonesian education system. The world of education is expected to be a driving force to facilitate character development, so that members of the community have an awareness of the harmonious and democratic life of the nation and state while still paying attention to the joints of the Unitary State of the Republic of Indonesia (NKRI) and social norms in society that have become a common agreement. The formulation of national education goals in Indonesia requires at least some foundations of national education. So it is hoped that this goal will have meaning, among these foundations are, religious foundation, scientific foundation, technological foundation, juridical foundation, sociological foundation, sociological foundation, psychological foundation, and cultural foundation.